2013
DOI: 10.1021/jo4003745
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Modular Boron Systems Based on NNN- and ONO-Tridentate Ligands: Self-Assembly and Cell Imaging

Abstract: We have synthesized a series of new fluorescent boron systems 1a-c and 2a-d based on nitrogen (NNN) or nitrogen and oxygen (ONO)-containing tridentate ligands. These novel dyes are characterized by high thermal and chemical stability. They show large Stokes shifts (mostly above 3200 cm(-1)) and quantum yields in solution and in the solid state up to 40%. The easy, modular synthesis facilitates the convenient variation of the axial substituent on the central boron atom, allowing the functionalization of this dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 57 publications
(32 reference statements)
0
19
0
Order By: Relevance
“…Therefore we decided to use the crude product 6e for further reactions since we know from experience that the triazapentadiene boron compounds are readily purified by either recrystallization or via column chromatography on alumina oxide. 15,21 Boron complexes 14a-e: the novel boron complexes derived from these ligands were synthesized by heating a solution of the respective triazapentadiene ligands 6a-e with 1 to 3 equivalents of triphenylborane in toluene under reflux for 5 hours (Scheme 4).…”
Section: Synthesismentioning
confidence: 99%
“…Therefore we decided to use the crude product 6e for further reactions since we know from experience that the triazapentadiene boron compounds are readily purified by either recrystallization or via column chromatography on alumina oxide. 15,21 Boron complexes 14a-e: the novel boron complexes derived from these ligands were synthesized by heating a solution of the respective triazapentadiene ligands 6a-e with 1 to 3 equivalents of triphenylborane in toluene under reflux for 5 hours (Scheme 4).…”
Section: Synthesismentioning
confidence: 99%
“…7 On the other hand, non-pyrrolic BODIPY analogues have recently attracted much interest and possess many advantages including the following: (1) readily available, cheaper and more stable starting materials; (2) easier synthesis, especially for the asymmetrical dyes and generally no oxidation step needed; (3) unparalleled diversity in structures; (4) larger Stokes shifts and better photostability of dyes. Thus, a variety of O,O-bi-, 8-10 N,N-bi-, 11,12 N,O-bi-, [13][14][15] O,N,O-tri-, 16,17 N,N,N-tri-, 17 and N,N,O,O-tetradentated 18 boron complexes have been efficiently synthesized and some show larger Stokes shifts with remarkable photostabilities.…”
Section: Introductionmentioning
confidence: 99%
“…So far, only limited BF 2 complexes of aza-BODIPY analogues have been reported. BF 2 complexes C and their π-extended boron complexes by Würthwein 17,19 and pyridine based dyes D, E and their derivatives by Fu, 20 and Zhu 21 all show high thermal, chemical stabilities and favorable photophysical properties. A class of BF 2 complexes F was recently synthesized by You and coworkers 22 through Pd catalyzed coupling reactions and showed mechanochromic luminescence.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the N→B coordinative bond facilitates the polarization of the electronic π-system, a situation that optimizes the third-order nonlinear optical (NLO) response. In addition, three boron complexes ( 65a – 65c ) were prepared by the reaction of bidentate ligands ( 66a – 66c ) and diphenylboronic acid ( Scheme 13 ) [ 69 ]. Compounds 58a and 58c were found to have a nonplanar conformation for the main p-backbone, acquired after boron complexation; for compound 58b , the planar conformation is preserved.…”
Section: O-b-n Boronatesmentioning
confidence: 99%